Tugas Akhir Karya Mango And Grapes In The City Of Probolinggo As An Idea For Creating Ready To Wear Batik Motifs - Muhammad Arif Jati Purnomo; Teguh Teguh Irawan (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
Batik motifs on ready-to-wear clothing in the form of mangoes and grapes in Probolinggo City are the goal of this final project. In creating this work, a method consisting of exploration, incubation, conceptualization and materialization was used. In creating a work, the process starts from the exploration stage. The next process is the embodiment stage, in this stage it starts with making clothing patterns, scratching, canting, fabric coloring, striping batik cloth, and sewing and finishing. The technique used in the process of creating the work is the dabbing and wiping technique. The materials used are wax (wax), canting, remasol, primissima cloth and toyobo cloth. The creation of ready-to-wear clothing is used in activities celebrating the anniversary of the city of Probolinggo, meetings with business partners. This clothing is used by men and women targeting adults aged 17-28. These works have their respective work titles taken from Sanskrit and existing fruit names. Work 1 with the title "Mider", work 2 with the title "Berawa", work 3 with the title "Andakara", work 4 with the title "Lalijiwo". This work was created with mango and grape motifs, applied to ready-to-wear clothing. In the process of realizing the ready to wear clothing design in the form of suits, trousers, skirts and trousers. Key Words : mango and grapes, batik motifs and ready to wear